KORELASI MEKANISME KOPING DENGAN KECEMASAN ORANG TUA NEONATUS DI RUANG NICU SALAH SATU RS RUJUKAN DI JAKARTA PUSAT - Melinna Nababan (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2026)
Neonatal intensive care is an experience that creates emotional stress and anxiety for parents due to the infant’s critical condition and the complex medical environment. Unmanaged anxiety may interfere with psychological adaptation and parental involvement in infant care. This study aimed to analyze the relationship between coping mechanisms and parental anxiety levels during neonatal care. A quantitative descriptive correlational design with a cross sectional approach was applied. The sample consisted of sixty seven parents selected using total sampling. Data were collected using coping mechanism and anxiety questionnaires and analyzed using the Spearman correlation test. The results demonstrated a significant relationship between coping mechanisms and anxiety levels, indicating that parents who applied adaptive coping strategies tended to experience lower anxiety. The conclusion of this study confirms that effective stress management through adaptive coping plays an important role in maintaining parental emotional stability during neonatal intensive care. It is recommended that health care providers enhance emotional support and education for parents, hospitals strengthen family oriented care services, and future studies explore other psychosocial factors using qualitative approaches.